Immobilization of probiotic cells in alginate and pectinate capsules - Voo, Wan Ping (2011)
A comparative study on the stability and the potential of alginate and pectin based capsules for production of poultry probiotic cells using MRS medium was conducted. The capsule cores, made of three types of materials, i.e. ca-alginate, ca-pectinate and ca-alginate/pectinate, were compared. The mechanical strength of ca-pectinate and ca-alginate/pectinate capsules was 2.5 and 4.3 times, respectively, of that of ca-alginate capsule. The pectin based capsules were found to be more stable than that of the alginate based capsules and their stability was further improved by chitosan coating. However, double layer coating of capsules did not improve the capsule stability due to the competing of polyanion material for chitosan binding, which had weakened the first layer coating. The cell concentration in pectin based capsules was comparable to that of the alginate based capsules. The maximum cell concentration of 1 x 109 CFU/ml was obtained with uncoated ca-alginate/pectinate capsules after two fermentation cycles. Cell concentration in capsules could be influenced by the gel network density since it determines the capsule stability and structural properties. On the other hand, pectin based capsules was found to give significantly lower cell concentration in the growth medium for the initial fermentation cycles due to its higher capsule stability if compared to that of alginate capsules. In conclusion, pectin was found to be potential encapsulation material for probiotic cell production owing to its stability, favourable microenvironment for cell growth as well as its potential to control the release of cells from capsules.